Ðe án thí diem REDD+ là gì?: Các loai hình de án thí diem REDD dua trên các hoat d og thí diem o Indonesia - Madeira, E.M.; Sills, E.; Brockhaus, Maria; Verchot, Louis V.; Kanninen, M. (Center for International Forestry Research, 2010)
This infobrief provides an early snapshot of 17 REDD+ pilots under development in Indonesia in mid 2009. There is great variety in and experimentation by the proponents of REDD+ pilots. Three key dimensions useful for categorising early pilots are: 1) degree of spatial planning and heterogeneity of forest classification, 2) strategy for establishing long-term claims to carbon, and 3) predominant driver and agent of deforestation and degradation. The prevalence of the concession model in this sample of REDD+ pilots is explained by its alignment with existing tenure regimes and with the requirement to demonstrate secure, long-term carbon tenure in order to sell credits in voluntary carbon markets. REDD+ pilots following the concession model risk carrying forward biases and constraints of the existing concession system, including the focus on production forests and the tendency to exclude smallholders from management decisions. Addressing the inequalities and inefficiencies of the existing tenure regime requires broader policy reform and larger-scale action than is likely to be achieved by individual pilots. High transaction costs deter the development of pilots that partner directly with smallholders to reduce emissions. New models and strategies should be developed to reduce these transaction costs, for example, by aggregating or bundling smallholder initiatives. Further research is needed both to assess outcomes of different pilot types and to update this typology to reflect the rapidly expanding number of REDD+ pilots and the rapidly evolving institutional and regulatory framework for REDD+ in Indonesia.